1998
DOI: 10.1002/hep.510270413
|View full text |Cite
|
Sign up to set email alerts
|

Variant liver estrogen receptor transcripts already occur at an early stage of chronic liver disease

Abstract: Variant estrogen receptors may be found in hepatocellular carcinoma and may influence its natural history. Because it is not known whether their occurrence is an early or a late event during the course of chronic liver disease or whether they cluster in some subgroups of patients, we investigated a series of patients in different stages of chronic liver disease. One hundred eleven consecutive patients were studied for variant estrogen receptor transcripts by reversetranscription polymerase chain reaction of RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…The severe prognosis of patients with HBV-related disease in comparison with the HCV-positive ones has been already recognized (Zaman et al, 1985;Villa et al, 1988). It is possible that in the present series this finding may be due to the preselection of patients with HCC characterized by variant ER receptors transcripts: these subjects are in fact significantly more often HBsAg-positive than HCV-positive (Villa et al, 1998). On the other hand, the capability of HBV to integrate into host genome might facilitate the occurrence of alternative splicing events of ER gene with onset of variant ERs.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The severe prognosis of patients with HBV-related disease in comparison with the HCV-positive ones has been already recognized (Zaman et al, 1985;Villa et al, 1988). It is possible that in the present series this finding may be due to the preselection of patients with HCC characterized by variant ER receptors transcripts: these subjects are in fact significantly more often HBsAg-positive than HCV-positive (Villa et al, 1998). On the other hand, the capability of HBV to integrate into host genome might facilitate the occurrence of alternative splicing events of ER gene with onset of variant ERs.…”
Section: Discussionmentioning
confidence: 79%
“…One possible reason for tamoxifen failure could reside in the presence, in a substantial percentage of patients with hepatocellular carcinoma (HCC), of variant liver oestrogen receptors (Villa et al, 1998): these receptors derive from an exon 5-deleted oestrogen receptor transcript which gives rise to an oestrogen receptor altered in the hormone-binding domain (vER), capable, however, of maintaining a constitutive transcriptional activity (Fuqua et al, 1991). Tumours characterized by this receptor have significantly shorter doubling time in comparison with tumours characterized by wild-type ER (wtER) transcripts, a higher clinical aggressiveness and are unresponsive to tamoxifen, as this drug acts blocking the receptor protein by competing for the hormone binding site and requires an intact receptor to exert its action (Villa et al, 1995(Villa et al, , 1996a(Villa et al, , 1996b.…”
mentioning
confidence: 99%
“…Although the possibility that estrogens enhance human hepatocarcinogenesis has been postulated (36), recent results failed to show a clear association between human HCC risk and plasma estradiol level and estradiol/testosterone ratio, whereas the risk of HCC was found to increase with plasma testosterone level (20). Variant forms of Er mRNA, lacking exon 5, probably associated with the loss of estrogen receptor responsiveness to estrogens, are expressed in human preneoplastic and neoplastic liver (37,38), and the relative expression of these forms seems to be associated with ominous prognosis (39). Polymorphic human ESR1 T29/T has recently been associated with persistent hepatitis B virus infection in a relatively small Chinese population (40).…”
Section: Discussionmentioning
confidence: 99%
“…3 The significantly higher occurrence of variant estrogen receptors in early-stage chronic liver disease, especially among HBV-infected men, suggests that alteration of estrogen receptors, favoring uncontrolled proliferation might play a role in neoplastic transformation of the liver. 37 Epidemiologic studies have found that increased exposure to estrogen is significantly associated with elevated HCC risk among women and that isoflavones may reduce estrogen levels. Significantly increased risks of primary liver cancer and of HCC, specifically, were found in case-control studies of ever-users and longterm users of oral contraceptives in the United States 38 and Italy.…”
Section: Discussionmentioning
confidence: 99%